A circulação do discurso da Amway: do controle à prática discursiva - Brunelli, Anna Flora [UNESP] (Pontifícia Universidade Católica de São Paulo (PUC-SP), 2013)
In this paper, we intend to contribute to the debate about the circulation of the discourses. To do that, we analyze aspects regarding the circulation of Amway's discourse, a North-American network sales company that has been working in Brazil for a while. Precisely, we analyze the conditions of this circulation at the time it was more intensively, ie, in the 90s, when there were thousands of people in several parts of the country selling the company's products or consuming them. This study has been based on French Discourse Analysis with focus on both Michel Foucault's insights on the control mechanisms of discourse and Maingueneau's reformulated notion of discursive practice. The analysis reveals that Amway's discourse displays features of a doctrine, and, as a discursive practice, it cannot be conceived of as separated from the subjects who convey it, nor from its hierarchical organization, nor from the events that the company promotes and those which are promoted under its name. In these terms, the analysis shows how the discourse is not only a set of texts, but also concerns to the institutional network related to the social group that the enunciation of discourse presupposes and makes it possible.

Neste trabalho, com o intuito de contribuir com as reflexões sobre a circulação dos discursos, analisamos aspectos relativos à circulação do discurso da Amway, uma empresa norte-americana de vendas em rede que tem atuado há um certo tempo no Brasil. Mais exatamente, analisamos as condições dessa circulação no momento em que ocorreu de modo mais intenso, isto é, na década de 90, quando havia milhares de pessoas em diversas partes do país envolvidas com a venda dos produtos da empresa e/ou com o seu consumo. Nosso estudo se baseia na Análise do Discurso de linha francesa, com ênfase nas reflexões de Foucault sobre os mecanismos de controle do discurso e na noção de prática discursiva, tal como reformulada por Maingueneau. A análise revela que o discurso da Amway apresenta aspectos de uma doutrina e que, como uma prática discursiva, não pode ser pensado de modo separado dos sujeitos que veiculam o discurso, do modo como os organiza numa hierarquia específica, nem dos eventos que promove e que são promovidos em nome da empresa. Nesses termos, a análise evidencia como os discursos dizem respeito não só a um conjunto de textos, mas também a uma rede institucional relativa ao grupo social que a enunciação do discurso supõe e torna possível.
The circulation of Amway's discourse: from control to social practice
Keywords: vendas em rede; circulação; doutrina; prática discursiva; network sales; circulation; doctrine; discursive practice